2020
DOI: 10.1001/jamapediatrics.2019.6235
|View full text |Cite|
|
Sign up to set email alerts
|

Patterns of Mean Age at Drug Use Initiation Among Adolescents and Emerging Adults, 2004-2017

Abstract: for editing assistance. He was compensated for his contribution. We thank the patients' families for granting permission to publish this information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 5 publications
(9 reference statements)
2
19
0
Order By: Relevance
“…It ranged from 20 to 21 years for cocaine, and 19 to 21 years for methamphetamine. The stable trend is consistent with results from the NSDUH [26], and the Monitoring the Future national survey [27]. This is also consistent with figures from other countries; in Australia, the median age of onset of cocaine and methamphetamine use is 22 and 20 years, respectively [28].…”
Section: Factors Associated With Age Of Onset Of Cocaine or Methamphetamine Usesupporting
confidence: 88%
“…It ranged from 20 to 21 years for cocaine, and 19 to 21 years for methamphetamine. The stable trend is consistent with results from the NSDUH [26], and the Monitoring the Future national survey [27]. This is also consistent with figures from other countries; in Australia, the median age of onset of cocaine and methamphetamine use is 22 and 20 years, respectively [28].…”
Section: Factors Associated With Age Of Onset Of Cocaine or Methamphetamine Usesupporting
confidence: 88%
“…The average age of first use of cannabis in Australia (18.7 years) is more than 3 years earlier than that of first-time opioid use (22.0 years) [7]. A similar order of initiation is also reflected in the average age of first use among users entering treatment in Europe (17.0 and 24.0 years) [8] and past 12-month adolescent substance users in the United States (16.4 and 16.6 years) [9]. Furthermore, longitudinal cohort studies have found that non-medical opioid use is rarely reported without prior cannabis use [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study from a large health care system with universal screening for prenatal cannabis use, Black women were three times more likely to report weekly cannabis use and four times more likely to report daily cannabis compared to Hispanic and white women (13). While women often report cannabis use during pregnancy to alleviate pregnancy related symptoms such as nausea and vomiting (Young-Wolff et al, 2018), most women initiate cannabis use well before pregnancy, by ages 16-18 (Alcover & Thompson, 2020;Chen et al, 2017). Additionally.…”
Section: Introductionmentioning
confidence: 99%